FAKTOR-FAKTOR YANG MEMPENGARUHI PENYERAPAN TENAGA KERJA PADA INDUSTRI RUMAH PANGGUNG KECAMATAN TOMPASO BARU, KABUPATEN MINAHASA SELATAN - Jeifi Indri Liow; Gene H. M. Kapantow; Mex L. Sondakh (Sam Ratulangi University, 2016)
This study aimed to analyze the factors affecting the number of workers in the wooden house indutry at Tompaso Baru, South Minahasa. The data used were primary data obtained from the 23 available wooden house enterprises in Tompaso Baru by using questionnaires. Data were analysed using multiple regression and a Cobb Douglass Model was apllied. The Factors that were analyzed including the wages, production values and capital. The preliminary analysis shows there was a high correlation (multicollinearity) between the production value and capital. It has been decided to drop the capital factor in further analysis. Results of the analysis showed that the models used were good enough to be used for analysis, indicated by the R2 value of 91.4% and a significant level of the model which was of less than 1%. Partial significant level of each factor, wages and production value, was also less than 1%. This showed that wages and production value were significant factors in the determining the number of workers recruited in the wooden house industry in Tompaso Baru. Both of them have positive directions, meaning that an increase in wages or production value would increase the number of workers in this industry.*ghmk*